High-precision sulfur isotope composition of enstatite meteorites and implications of the formation and evolution of their parent bodies. (1st January 2016) - Defouilloy, C.; Cartigny, P.; Assayag, N.; Moynier, F.; Barrat, J.-A.
Abstract: In order to better understand the formation and evolution of their parent bodies, the three isotope ratios of sulfur were analyzed in 33 enstatite meteorites (24 enstatite chondrites and 9 aubrites). The results show that on average all enstatite chondrite groups are enriched in the lightest isotopes compared to other chondrite groups, with means of δ 34 S of −0.28 ± 0.22‰ for EH3/4, −0.16 ± 0.16‰ for EH5, −0.32 ± 0.15‰ for EL3, −0.67 ± 0.16‰ for EL6 and −0.64 ± 0.00‰ for EL7 (all 1 σ ). Aubrites show a larger isotope variability in their composition, with a δ 34 S varying from −1.350‰ to +0.154‰. Contrary to previously published results, our data show a distinct composition for EL6 compared to other enstatite chondrites. This could be related to an impact-induced loss of isotopically heavy oldhamite (δ 34 S = by 3.62 ± 3.02‰ (1 σ )) on the EL parent body. Although the bulk sulfur in both enstatite meteorites and aubrites does not show any significant Δ 33 S and Δ 36 S, the oldhamite fraction shows clear evidence of mass independent fractionation on the 36 S/ 32 S ratio (in 3 out of 9 analyzes, Δ 36 S up to +2.2‰), a signal that is not correlated to any 33 S/ 32 S anomaly (in 1 out of 9 analyzes, Δ 33 S down to −0.085‰). Though a nebular or photochemical origin cannot be ruled out, the most plausible mechanism to produce such isolated non-mass dependent 36 S/ 32 S anomalies would be a contribution of FeCl2 containing excesses of 36 S due to the decay of 36 Cl to the leached oldhamite fraction. Even though the sulfur isotopic composition measured in enstatite meteorites is distinct from the Bulk Silicate Earth (BSE), the isotopically lightest samples of EL6, EL7 and aubrites are approaching the isotopic composition of the BSE and enstatite meteorites remain the meteorites with the sulfur isotopic composition the closest to the terrestrial one.